Grid integration of intermittent renewable energy sources using price-responsive plug-in electric vehicles - David Dallinger; Martin Wietschel (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2011)
Plug-in electric vehicles (PEVs) are expected to balance the fluctuation of re-newable energy sources (RES). To investigate the contribution of PEVs, the availability of mobile battery storage and the control mechanism for load man-agement are crucial. This study therefore combined the following: a stochastic model to determine mobility behavior, an optimization model to minimize vehicle charging costs and an agent-based electricity market equilibrium model to esti-mate variable electricity prices. The variable electricity prices are calculated based on marginal generation costs. Hence, because of the merit order effect, the electricity prices provide incentives to consume electricity when the supply of renewable generation is high. Depending on the price signals and mobility behavior, PEVs calculate a cost minimizing charging schedule and therefore balance the fluctuation of RES. The analysis shows that it is possible to limit the peak load using the applied control mechanism. The contribution of PEVs to improving the integration of intermittent renewable power generation into the grid depends on the characteristic of the RES generation profile. For the Ger-man 2030 scenario used here, the negative residual load was reduced by 15 to 22 percent and the additional consumption of negative residual load was be-tween 34 and 52 percent.
urn:nbn:de:0011-n-1783381
Keywords: 330; Plug-in electric vehicles; demand-side management; variable prices; intermittent generation; Elektrofahrzeug; Elektrizitätswirtschaft; Regenerative Energie; Demand-Side Management